Experimental murine models of brainstem gliomas. Issue 5 (May 2022) - Ni, Shuting; Chen, Rujing; Hu, Kaili
Highlights: Brainstem glioma (BG) is a highly aggressive malignancy with poor prognosis. The preclinical model acts as important experimental systems to explore BG. Efficient onset and reproducible survival curves are important to BG models. A reliable preclinical model of BG is urgently needed for new drug discovery. Abstract : As an intractable central nervous system (CNS) tumor, brainstem glioma (BG) is one of the leading causes of pediatric death by brain tumors. Owing to the risk of surgical resection and the little improvement in survival time after radiotherapy and chemotherapy, there is an urgent need to find reliable model systems to better understand the regional pathogenesis of the brainstem and improve treatment strategies. In this review, we outline the evolution of BG murine models, and discuss both their advantages and limitations in drug discovery.